An assessment of ecosystem services for the Brazilian Pantanal and Upper Paraguay River Basin: Socioeconomic instruments for biodiversity conservation and the sustainable use of natural resources - Fábio Padilha Bolzan (2023)
This thesis addresses the importance of valuing ecosystem services (ES) as well as the spatialization of Nature's Contributions to People (NCP), using the Brazilian Pantanal and the Upper Paraguay Basin as a model. We highlight the challenges faced in the management and conservation of ES in these regions, including the need for public policies that recognize the value of nature's contributions to people (NCP). Nature's contributions to people in the Pantanal and Upper Paraguay Basin include material benefits such as food, water, wood, and medicine, as well as non-material benefits such as recreation, tourism, spirituality, and mental health. We address the importance of valuing and spatializing nature's contributions as powerful tools for developing strategies and policies that balance economic growth with environmental protection in our study area. We discuss the main challenges and opportunities of ES monetization and how the congruence or divergence between people's needs for nature's contributions can be an interesting model used to support decision-making by both public and private entities in a more assertive and efficient way.